Non symptomatic atrial septal defect venosus type IVC – SV coexistent with non-obstructed foramen ovale in 78 years old patient – a case report - Weronika Sandra Topyła; Beata Krasuska; Wioletta Anna Bal; Tomasz Krzysztof Bąk; Agnieszka Zofia Staciwa (Journal of Education, Health and Sport, 2017)
Atrial septal defect may be seen under few forms. The most common is ASD secundarum – about 70% of defects. Coexistent non-obstructed foramen ovale with atrial septal defect venosus type IVC – SV is very rare. Untreated atrial septal defect can be associated with numerous complications and with significantly shortened life expectancy. Patients with the increased left-to-right shunting may occasionally present congestive heart failure with pulmonary hypertension in their fourth to sixth decades of life. Late problems in untreated patients also include the risk of paradoxical embolus as well as atrial fibrillation, pulmonary hypertension and right heart failure. The presented medical case is an example of a very rare clinical disease in which a complex heart defect within the atrial septum is asymptomatic, does not give any complications and does not require treatment.